"Именно благодаря его настойчивости и отзывчивости в Киеве многое было налажено для ... улучшения быта сотен несчастных сирот и полусирот военного времени..." (спогади Є. Ю. Спаської про знайомство з І. Г. Еренбургом) - Луговик, Т. В. (Видавництво НДУ ім.М. В. Гоголя, 2017)
У статті висвітлено спільну благодійну діяльність в часи Першої світової війни видатної дослідниці народного мистецтва Є. Ю. Спаської та письменника І. Г. Еренбурга. Досліджено громадсько- благочинну роботу Є. Ю. Спаської в складі Відділу допомоги населенню Всеросійського земського союзу. Схарактеризовано Є. Ю. Спаської щодо покращення умов існування евакуйованого населення.
The article, based on archival materials, researched social activities of outstanding researcher of folk art, anthropologist, ethnographer, ethnologist and Museum curator Evgenia Yurievna Spassky during the First World war. Lighted charitable work of the scientist within the division of assistance to the population of the all-Russian Zemstvo Union. Found part. Е. Yu. Spassky in selfless actions for preservation and promotion of historical and cultural heritage of Ukraine. Considered familiarity and joint charity work Е. Yu. Spassky and prominent public figure І. G. Erenburg. Traced a set of measures developed Е. Yu. Spassky for the sake of improving living conditions for the evacuated population, in particular the socially vulnerable categories. Describes the role and place Е. Yu. Spassky in charity activities of the all-Russian Zemstvo Union.
Keywords: Перша світова війна; Революція 1917 р.; Всеросій- ський земський союз; World war; revolution of 1917; Russian Zemsky Union